Altered Domain Functional Network Connectivity Strength and Randomness in Schizophrenia - Vergara, Victor M.; Damaraju, Eswar; Turner, Jessica A.; Pearlson, Godfrey; Belger, Aysenil; Mathalon, Daniel H.; Potkin, Steven G.; Preda, Adrian; Vaidya, Jatin G.; van Erp, Theo G. M.; McEwen, Sarah; Calhoun, Vince D. (Frontiers in Psychiatry, 2019)
Functional connectivity is one of the most widely used tools for investigating brain changes due to schizophrenia. Previous studies have identified differences in whole brain connectivity of schizophrenia patients. This study tests the existence of effects on domain-level functional network connectivity. Domain functional network connectivity looks for functional connectivity measures of groups of brain networks. This work considers two domain measures: functional connectivity strength and randomness. The first measure is simply an average of connectivities within the domains. The second assesses randomness of the domain specific connectivity matrix. Domains with less random connectivity have higher chance of exhibiting a biologically meaningful connectivity pattern. Consistent with prior observations, individuals with schizophrenia showed aberrant connectivity between subcortical, cerebellar and sensorial brain areas. They also showed lower connectivity between subcortical-cerebellum and default mode-sensorial areas. Compared to healthy volunteers, connectivity between cognitive and default mode domains showed less randomness, while connectivity between default mode-sensorial areas showed more randomness in schizophrenia. These differences in connectivity patterns suggest deleterious trade-offs in rewiring between important brain processing areas with more random connections with sensorial brain areas.